I en monarki är det en vanlig familj som sitter på tronen - Ljuslinder, Karin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
In this article I discuss the symbolic representations of the "family"-concept within the media reporting of the Swedish royal family which, I claim, trivialize and disguise political-economic dominance. The material consists of a recurrent TV-series, The Year with the Royal Family, 1978-2008. Like Michael Billig (1998) I mean that media representations of the royal family are stories about much more than only a celebrity-family. They are also symbolic representations of the nation as a family, unity, integration and national identity and thereby contributions to the reproduction of existing cultural values of these concepts. Through the trivial depictions of the royal family as an ordinary family the general public is daily reminded, in a subtle way, that they are members of a nation and what kind of values are important in the Swedish nation. I agree with Billig (1998) that the reason that this, so called banal nationalism, have survived is because the royal family has awaked very little academic interest. Thereby the media representations have been unchallenged.